The Influence of Health Education on Interest in Cervical Cancer Screening in Women of Reproductive Age at the Daruba Community Health Center, Morotai Islands Regency - Nurima Dano Mas'ud; Reny Retnaningsih (STIKES Columbia Asia Medan, 2025)
Cervical cancer remains a major public health problem among women, particularly in developing countries such as Indonesia, where morbidity and mortality rates are still high. Although effective screening methods are available, participation among women of reproductive age remains low due to limited awareness, knowledge, and interest in early detection. Health education is considered a key strategy to improve women’s understanding and encourage preventive behavior. This study aims to analyze the effect of health education on women’s interest in cervical cancer screening at the Daruba Community Health Center, Morotai Islands Regency. The research employed a quasi-experimental design with a one-group pretest–posttest approach. The population consisted of reproductive-age women visiting the health center, with a total sample of 40 respondents selected using total sampling techniques. The intervention involved structured health education sessions covering cervical cancer risks, prevention, and screening procedures. Data on screening interest were collected before and after the intervention using validated and reliable questionnaires. Data analysis was conducted descriptively and inferentially using the Wilcoxon Signed Rank Test with a significance level of 0.05. The results showed a significant increase in women’s interest in cervical cancer screening after the intervention (p < 0.05). These findings indicate that health education effectively improves awareness and motivation. Integrating routine education into primary health services is recommended to enhance early detection coverage and support cervical cancer prevention programs, especially in island regions.